The emergence of modern architecture : a documentary history from 1000 to 1810 - Lefaivre, Liane; Tzonis, Alexander (Routledge, 2004)
The book records a cognitive history of the emergence of modern architecture. Cutting across disciplinarian and institutional divisions as we know them today.